Peroral endoscopic remyotomy for failed Heller myotomy: a prospective single-center study - Zhou, P. H.; Li, Q. L.; Yao, L. Q.; Xu, M. D.; Chen, W. F.; Cai, M. Y.; Hu, J. W.; Li, L.; Zhang, Y. Q.; Zhong, Y. S.; Ma, L. L.; Qin, W. Z.; Cui, Z. (Endoscopy, 2013)
Background and study aims: Recurrence/persistence of symptoms occurs in approximately 20 % of patients after Heller myotomy for achalasia. Controversy exists regarding the therapy for patients in whom Heller myotomy has failed. The aim of the current study was to evaluate the efficacy and feasibility of peroral endoscopic myotomy (POEM), a new endoscopic myotomy technique, for patients with failed Heller myotomy. Patients and methods: A total of 12 patients with recurrence/persistence of symptoms after Heller myotomy, as diagnosed by established methods and an Eckardt score of ≥ 4, were prospectively included. The primary outcome was symptom relief during follow-up, defined as an Eckardt score of ≤ 3. Secondary outcomes were procedure-related adverse events, lower esophageal sphincter (LES) pressure on manometry, reflux symptoms, and medication use before and after POEM.Results: All 12 patients underwent successful POEM after a mean of 11.9 years (range 2 – 38 years) from the time of the primary Heller myotomy. No serious complications related to POEM were encountered. During a mean follow-up period of 10.4 months (range 5 – 14 months), treatment success was achieved in 11/12 patients (91.7 %; mean score pre- vs. post-treatment 9.2 vs. 1.3; P < 0.001). Mean LES pressure was 29.4 mmHg pre-treatment and 13.5 mmHg post-treatment (P < 0.001). One patient developed mild reflux symptoms and required intermittent medication with proton pump inhibitors.Conclusions: POEM seems to be a promising new treatment for failed Heller myotomy resulting in short-term symptom relief in > 90 % of cases. Previous Heller myotomy may make subsequent endoscopic remyotomy more challenging, but does not prevent successful POEM.